Follow up results of treatment of unstable angina by coronary angioplasty. Issue 5 (May 1987) - Steffenino, G; Meier, B; Finci, L; Rutishauser, W
Abstract : Eighty nine of 327 consecutive patients undergoing coronary angioplasty at a centre had unstable angina--defined as either a worsening of the frequency or the severity of chest pain or severe episodes of chest pain at rest with no evidence of acute myocardial infarction. Multivessel disease was present in 31 of these patients. Two or more vessels were dilated in the same procedure in one fifth of the patients. Primary success was obtained in 80 (90%) patients. Acute myocardial infarction was a complication in four (5%) patients, including two of four patients who needed emergency coronary bypass grafting. Follow up coronary angiography at a mean (SD) of 10 (6) months in 57 patients showed restenosis in 21 (37%): of these, 13 patients had repeat coronary angioplasty and three had elective coronary bypass grafting. All patients in whom angioplasty was initially successful were followed up for 10 (6) months after the last angioplasty procedure. There were no deaths. One patient had sustained a myocardial infarction unrelated to the dilated vessel. Clinically, 74 patients improved by at least one New York Heart Association class and 40 (50%) were symptom free and with no signs or symptoms of myocardial ischaemia on a stress test. Coronary angioplasty offers long term symptomatic improvement at an acceptable risk in the majority of patients with unstable angina.